Pemberlakuan Pidana Mati Bagi Pelaku Tindak Pidana Kekerasan Seksual Terhadap Anak dalam Upaya Perlindungan Hak Anak - Kantosa, Melia; Yoserwan, Yoserwan; Elvandari, Siska (Universitas Ekasakti, 2023)
Sexual violence is a form of crime in society whose development is increasingly diverse in terms of its motives, nature, form, intensity and modus operandi. As a social reality, the problem of sexual violence cannot be avoided and has always existed, giving rise to anxiety, because sexual violence is considered a disturbance to the welfare of society and its environment. Cases of sexual violence that are rife at this time occur in early childhood committed by Herry Wirawan against 13 of his female students, this can cause deep trauma and destroy a child's future. The form of law enforcement for Herry Wirawan is being sentenced to death. However, the National Commission for the Protection of Human Rights had given a rejection and protection of human rights to Herry Wirawan's death penalty because it was considered that this sentence was not in accordance with human rights. To answer this question, it is necessary to know how the death penalty exists in the new Criminal Code and what forms of legal protection for victims and children resulting from sexual violence committed by Herry Wirawan. This research is a type of legal research using a normative juridical legal research approach. The results of this study indicate that the death penalty provisions in the new Criminal Code are no longer the same as capital punishment in the Dutch heritage Criminal Code. Death penalty in the Dutch heritage Penal Code is known as the main criminal sanction with the first order, while the death penalty in the new Penal Code is no longer a type of principal punishment but only as an alternative punishment for certain criminal acts specified in the law. And the perpetrator was sentenced to death to pay restitution of Rp. 322,923,122.00 and confiscated all of Herry Wiwan's assets/assets to be used for the education and survival costs of the victims' children and their babies until they were adults and married.